Evaluation Transplantation of Bone-Derived Mesenchymal Stem Cell in the Patients with Hepatitis C-Related Liver Cirrhosis (Pi lot Study) - S. P. Lukashyk; O. V. Aleinikova; V. M. Tsyrkunov; I. A. Karpov; Y. I. Isaykina; O. V. Krasko (SINAPS LLC, 2021)
Introduction. Liver cirrhosis (LC) is the final stage in the progression of chronic diffuse diseases. As common, late stages of LC do not respond to conservative treatment methods, so liver transplantation is the most effective method at this stage. Widespread use of transplantation in clinical practice is due to serious obstacles: a shortage of donor organs, transplant rejection, complications during the operation and the postoperative period, as well as the high cost of such an intervention. We consider bone marrow stem cell transplantation as a potential treatment for liver cirrhosis and additional clinical trials for efficacy and safety.The aim of the study was to assess the efficacy and safety of intraparenchymal transplantation of autologous MSCs from the bone marrow for the treatment of patients with cirrhosis of the liver caused by the hepatitis C virus (HCV-LC).Materials and methods. A pilot open-label non-randomized prospective study with the inclusion of 6 patients with HCV-LP. Autologous MSCs were transplanted intraparenchymally into the liver tissue at the rate of 1x106/kg body weight - 1 ml at 5 points.Results. By 6 months after transplantation, there has been a decrease in the level of bilirubin (from 36,4 μmol/L to 27 μmol/L, p=0.03), MELD scores (from 11,5 to 8, p=0.035), and an increase in platelet levels by 3 months (from 83x109 / l to 124,6x109/l, p=0,031) and 6 months (up to 119,5x109/l, p=0,031). By 6 months after transplantation, there has been no statistically significant result in changing on points on the Child-Pugh scale (p=0,181), cytolysis indicators (maintaining elevated levels of ALT (p=0,062) and AST (p=0,844)), replicative activity of the virus (рreservation of HCV RNA in the blood) (p=0,219 ). Moreover, introduction of MSCs by 6 months after transplantation did not lead to resolution of liver cirrhosis and inflammatory infiltration according to light microscopy data, as well as to resolution of sinusoidal capillarization (p=0,586) and PCI transdifferentiation into myofibroblasts (p>0,99) according to immunohistochemical studies. None of the procedures after the transplantation had an increase in body temperature, an increase in laboratory parameters, or changes in vital functions. One patient was admitted to hospital after 6 months. after MSC transplantation, deep vein thrombosis of the right leg was diagnosed.Conclusion. The positive effect of MSCs on the improvement of liver function was noted. There was no effect on the replicative activity of the virus. The continuing activity of the inflammatory process was observed. The used MSC transplantation technique is a safe procedure for patients with HCV-LC severity classes A and B and can be applied in clinical practice.